Combined effect of deficit irrigation with saline water affects gas exchange, phytochemical profiles, antioxidant activities and grain yield of barley landraces "Ardhaoui" at heading stage. (4th May 2021) - Bagues, Mohamed; Zaghdoud, Chokri; Hafsi, Chokri; Boussora, Faiza; Triki, Tebra; Nagaz, Kamel
Abstract: Drought and salinity are the two major abiotic stresses limiting barley growth and productivity. In order to understand the physiological and biochemical traits associated with deficit irrigation using saline water in barley at heading stage, this study was performed under field conditions to treat two barley landraces, "Karkeni" (origin: irrigated) and "Bengardeni" (origin: rainfed in arid area), with three irrigation treatments as a function of cultural evapotranspiration ETc (T0: 100% ETc, T1: 75% ETc and T2: 50% ETc). In both barley landraces, deficit irrigation with saline water (T1 and T2 treatments) significantly decreased net photosynthetic rate (A), transpiration rate (E), stomatal conductance (gs), K + content, K + /Na + ratio and grain yield (GY); by contrast, DPPH and ABTS scavenging capacities as well as Na + content were increased, concomitant with a landrace-dependent variation in phenolic compounds composition. Interestingly, under T1 and T2 treatments, "Karkeni" had the lowest A, E, gs and K + /Na + ratio, and the highest Na + content and GY. Overall, at heading stage, salt accumulation in deficit irrigated soils with saline water significantly reduces GY of barley by influencing gas exchange, phytochemical profiles and antioxidant activities, in a landrace-dependent manner.